"Dulling the Edges": Young Men's Use of Alcohol to Deal With Grief Following the Death of a Male Friend. (February 2016) - Creighton, Genevieve; Oliffe, John; Matthews, Jennifer; Saewyc, Elizabeth
Background . The death of a male friend can be challenging for men because expressions of grief can be governed and restrained by dominant ideals of masculinity. It is common for young men to engage in health risk practices, such as alcohol overuse, to deal with feelings of sadness. Objective . This qualitative study investigated the ways that young men use alcohol in the process of grieving the accidental death of a male friend. Method . Participants included 35 men 19 to 25 years old and 22 men 26 to 35 years old who participated in individual semistructured interviews between 2010 and 2012. Results . Methodology informed by grounded theory and narrative analysis was used to analyse and interpret the transcribed interviews, focusing on the ways that men used alcohol in the grief process. Through data analysis we inductively derived three themes: (1) Using Alcohol to Dull the Pain, (2) Using Alcohol to Purge Sadness, and (3) Troubled Drinking . Conclusions: This study provides evidence to show that men's binge drinking following tragic loss is a means to express emotion and connect with others. Health interventions for young men who have lost a male peer need to be sensitive to gendered norms that inform grief practices and work with them to discern pathways toward recovery that promote long-term wellness.